Analysis of Relative Levels of Production of Pertussis Toxin Subunits and Ptl Proteins in Bordetella pertussis - Cheung, Anissa M. (American Society for Microbiology, 2004)
Pertussis toxin is transported across the outer membrane of Bordetella pertussis by the type IV secretion system known as the Ptl transporter, which is composed of nine different proteins. In order to determine the relative levels of production of pertussis toxin subunits and Ptl proteins in B. pertussis, we constructed translational fusions of the gene for alkaline phosphatase, phoA, with various ptx and ptl genes. Comparison of the alkaline phosphatase activity of strains containing ptx′- or ptl′-phoA fusions indicated that pertussis toxin subunits are produced at higher levels than Ptl proteins, which are encoded by genes located toward the 3′ end of the ptx-ptl operon. We also engineered strains of B. pertussis by introducing multiple copies of the ptl genes or subsets of these genes and then examined the ability of each of these strains to secrete pertussis toxin. From these studies, we determined that certain Ptl proteins appear to be limiting in the secretion of pertussis toxin from the bacteria. These results represent an important first step in assessing the stoichiometric relationship of pertussis toxin and its transporter within the bacterial cell.